Particle dynamics in a gas assisted coal combustion chamber using advanced laser diagnostics. (1st June 2020) - Becker, Lukas G.; Pielsticker, Stefan; Böhm, Benjamin; Kneer, Reinhold; Dreizler, Andreas
Highlights: Advancement of simultaneous PTV/PIV in solid fuel combustion. Simultaneous two phase velocity measurements inside a coal flame. Improved understanding of interaction between devolatilization and two phase flow. Measurements in regions of utmost importance for stabilization of coal flames. Abstract: Coal combustion is strongly influenced by the interaction of gas phase turbulence, particle dynamics and chemistry. To advance the understanding of these mutually coupled processes, experiments under well-controlled inflow and boundary conditions are needed that provide access to non-intrusive multi-parameter measurement techniques. Following this idea, in this work gas-assisted coal flames with power up to 40 kWth are investigated in an optically accessible combustion chamber including a quartz glass quarl of the swirl burner assembly. A Two-phase particle image/tracking velocimetry (PIV-PTV) technique is applied for the first time in coal combustion to measure simultaneously velocities of small and large particles. Due to the wide particle size distribution of the grinded coal small particles can be used as tracers for the gas flow while the velocity of large particles can be measured with particle tracking velocimetry (PTV) simultaneously. For this purpose Mie-scattering is imaged by a single camera. Large and small particles are separated in the post-processing based on apparent size and signal intensity of each particle individually. By measuring quasi-simultaneously laser-induced fluorescence of intermediate hydrocarbons released from coal particles during their devolatilization process, regions of intense pyrolysis are identified. Flames operated with different coal types and thermal powers in air and oxy-fuel atmospheres are compared to each other. Additionally, advantages and limits of the measurement techniques are discussed in the context of coal combustion.